Strategis Koperasi Nelayan dalam Optimalisasi Pendapatan Anggota (Studi Kasus: Desa Hilir Muara) - Kintan Permata Sari; Budi Suryadi (JURNAL BISNIS DAN PEMBANGUNAN, 2025)
Abstract: Kotabaru Regency, a Strategic Provincial Area for marine and capture fisheries, boasts significant potential, with a fishery production of 65,554 tons in 2023, the highest in South Kalimantan. Hilir Muara Village, located in Pulau Laut Sigam Sub-district, serves as a marine-based economic hub driven by fishermen cooperatives, with KUB Matahari Bersinar as the primary collective institution. Despite high production, fishermen‘s income remains low, ranging from IDR 1,500,000 to IDR 2,000,000 per month, below Kotabaru‘s minimum wage of IDR 3,462,000 (BPS, 2023). KUB Matahari Bersinar faces challenges, including limited working capital, weak managerial capacity, insufficient technical training, and low adoption of modern technology. Previous studies have largely focused on macro-level fisheries or national seafood exports, with limited research on strategies for small-scale local fishermen cooperatives. This study aims to identify the strengths, weaknesses, opportunities, and threats of the KUB Matahari Bersinar through a SWOT analysis. The analytical modeling produces a strategic matrix of SO–WO–ST–WT strategies based on IFAS–EFAS scores, and formulates cooperative strengthening strategies to optimize member income. Using a qualitative approach through interviews, observations, and document reviews, the study finds that strategies based on local potential—such as modernization of fishing technology, digitalization of management, and strengthening of market access—can improve the welfare of fishermen. The results of this study are expected to provide practical contributions to the development of fishermen cooperatives in Kotabaru Regency